2017
DOI: 10.1530/joe-16-0598
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal muscle insulin resistance: role of mitochondria and other ROS sources

Abstract: At present, obesity is one of the most important public health problems in the world because it causes several diseases and reduces life expectancy. Although it is well known that insulin resistance plays a pivotal role in the development of type 2 diabetes mellitus (the more frequent disease in obese people) the link between obesity and insulin resistance is yet a matter of debate. One of the most deleterious effects of obesity is the deposition of lipids in non-adipose tissues when the capacity of adipose ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
114
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 222 publications
(118 citation statements)
references
References 281 publications
4
114
0
Order By: Relevance
“…Indeed, NRG1 was shown to attenuate oxidative stress in microglial and cardiac cells 50, 51 . It is also well accepted that increased mitochondrial ROS production is associated with insulin resistance and diabetes 52 . Moreover, excess of ROS production may promote calcium homeostasis impairment leading to contractility defect 5355 .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, NRG1 was shown to attenuate oxidative stress in microglial and cardiac cells 50, 51 . It is also well accepted that increased mitochondrial ROS production is associated with insulin resistance and diabetes 52 . Moreover, excess of ROS production may promote calcium homeostasis impairment leading to contractility defect 5355 .…”
Section: Discussionmentioning
confidence: 99%
“…However, mitochondria isolated from insulin resistant adipose or muscle tissue generate higher rates of ROS production per unit of substrate (78) suggesting there may be changes within mitochondria that promote ROS production or lower ROS scavenging. Defects in oxidative phosphorylation can increase ROS production yet a number of studies have reported no change in or improved mitochondrial oxidative capacity in insulin resistance (reviewed in (137)(138)(139), (78,83,140)), suggesting that changes in the oxidative phosphorylation pathway are unlikely to be a primary driver of ROS under these conditions. We recently identified a deficiency in coenzyme Q, a cofactor that transfers electrons from Complexes I and II to Complex III of the electron transport chain, in insulin resistant adipose and muscle tissue (83).…”
Section: Why Are Mitochondrial Ros Elevated In Insulin Resistance?mentioning
confidence: 99%
“…The proximal ROS from the electron transport chain is superoxide, but this is rapidly dismutated by SOD2 to hydrogen peroxide and both superoxide and hydrogen peroxide are implicated in causing insulin resistance (132,138). It is not clear whether a specific form of ROS or a specific site of ROS production in mitochondria is responsible for conferring insulin resistance.…”
Section: Why Are Mitochondrial Ros Elevated In Insulin Resistance?mentioning
confidence: 99%
“…Currently, the causes of insulin resistance remain largely unclear, while multiple internal abnormalities seem to contribute to, including the loss-of-function mutation of IR , transduction impairment by obesity-related inflammation and toxic effects of metabolites by overloaded fatty acid or glucose. All these possible mechanisms could destroy the structure or activity of pathway molecules, hence inducing signaling insensitivity [137]. Patients with insulin resistance often suffer from hyperinsulinemia, hyperglycemia, hyperuricemia and dysfunctional lipid metabolism, which may evolve into metabolic disorders such as type 2 diabetes mellitus (T2DM), polycystic ovary syndrome (PCOS) and atherosclerosis [138, 139].…”
Section: Major Cancer-related Signaling Pathways With Links To Ad mentioning
confidence: 99%